Students' Interest In Investing In The Sharia Capital Market - Hafidhah; Furqani, Hafas; Millati, Aja Fitria (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2023)
The Indonesia Stock Exchange (IDX) stated that youth, including students, have considerable potential to become stock investors. One of the main targets of capital market investors and Islamic capital markets is students. This study aims to determine whether knowledge, Socialization, and education influence the interest in investing in the Islamic capital market students of the Faculty of Islamic Economics and Business Ar-Raniry State Islamic University Banda Aceh. This research is a quantitative study in which samples were taken from as many as 332 respondents using a probability sampling technique. This probability sampling technique includes several techniques, but the researcher chose the simple random sampling technique because the sample members from the population were taken randomly without regard to the strata in the population. The data type used is primary data, which distributes the questionnaire via Google Forms. The research data analysis method used the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach and SmartPLS software's help. The results of this study indicate that the knowledge variable has a positive and significant effect on the interest in investing in the Islamic capital market. The socialization variable also has a positive and significant effect on the interest in investing in the Islamic capital market, and the education variable also has a positive and significant effect on the interest in investing in the Islamic capital market. Based on the R2 test, the influence exerted by the independent variables (knowledge, outreach, and education) on the dependent variable (intention to invest in the Islamic capital market) is 52.4%. In contrast, the rest is influenced by other variables not included in this study.